The little inn at the crossroads: a spiritual approach to the design of a leadership course - Bento, Regina F. (2000)
"Leading from within" cannot be taught, yet it must be learned. This is the story of how a metaphor was used to address this paradox in the design of a graduate course that explored the spiritual dimensions of leadership. The course was designed as a little inn at the crossroads where our life journeys would converge. Here you will get a glimpse of the inn's virtual library (with our Web-based reading materials); the studio (where a variety of personal products were created each week); and most important, the seven workshops where each week the spirit of leadership was explored. - Reproduced
Keywords: Leadership